2013
DOI: 10.1080/10550887.2012.759872
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study Comparing Methadone and Buprenorphine in Patients with Chronic Pain and Coexistent Opioid Addiction

Abstract: Patients with opioid addiction who receive prescription opioids for treatment of chronic non-malignant pain present a therapeutic challenge. Fifty-four patients with chronic pain and opioid addiction were randomized to receive methadone or buprenorphine/naloxone. At the 6-month follow-up, 26 (48.1%) participants who remained in the study noted a 12.75% reduction in pain (P = 0.043) and compared to 5 in the buprenorphine group, none in the methadone group reported illicit opioid use (P = 0.039). Other differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 25 publications
4
77
0
1
Order By: Relevance
“…In our sample, attitudes towards both medications, among those who had experience with both, provided further evidence of the general favorability of buprenorphine over methadone. Finally, as others have also noted, we found that treating pain with co-occurring substance use remains a challenge both for patients and clinicians (Neumann et al, 2013; Weiss et al, 2014). …”
Section: Discussionsupporting
confidence: 67%
“…In our sample, attitudes towards both medications, among those who had experience with both, provided further evidence of the general favorability of buprenorphine over methadone. Finally, as others have also noted, we found that treating pain with co-occurring substance use remains a challenge both for patients and clinicians (Neumann et al, 2013; Weiss et al, 2014). …”
Section: Discussionsupporting
confidence: 67%
“…17 While buprenorphine has analgesic properties, it is not typically initiated, dosed, or directed toward pain relief in opioid-dependent persons. [21][22][23][24] Persistent pain is associated with negative substance use outcomes in persons receiving buprenorphine for opioid detoxification 25 or as maintenance treatment. 12 Unrelieved chronic pain contributes to early buprenorphine treatment termination.…”
Section: Introductionmentioning
confidence: 99%
“…Misclassification of medications could occur, e.g. , benzodiazepines might be used for anticonvulsant purposes and as sleeping aid, while methadone could be used for substance-related disorders and pain control (48). Lastly, selection bias was also possible since the subjects were enrolled from four different research centers and each center, and clinician might have different opinions for defining active SRD.…”
Section: Discussionmentioning
confidence: 99%